Strategi Pengembangan Agribisnis Kentang Merah di Kabupaten Solok - Fauzi, Dian; Baga, Lukman Mohammad; Tinaprilla, Netti (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
The purpose of this research was to formulate the strategy of developing agribusiness of red potato in Solok Regency. The research was conducted on the district which has highest production of red potato in Solok Regency, Lembah Gumanti District. The method used on this research was SWOT matrix analysis and architectural strategic analysis. Based on SWOT analysis matrix, ten strategies were recommended in order to develop the agribusiness of red potato in Solok regency. From those ten strategies, sixteen recommended program was formulated based on analytical research. These programs were divided intoÂ  two, routine running program and gradually running program.